Explaining the gender wage gap: Estimates from a dynamic model of job changes and hours changes - Kai Liu (Quantitative Economics, 2016)
I address the causes of the gender wage gap with a new dynamic model of wage, hours, and job changes that permits me to decompose the gap into a portion due to gender differences in preferences for hours of work and in constraints. The dynamic model allows the differences in constraints to reflect possible gender differences in job arrival rates, job destruction rates, the mean and variance of the wage offer distribution, and the wage cost of part-time work. The model is estimated using the 1996 panel of the Survey of Income and Program Participation. I find that the preference for part-time work increases with marriage and number of children among women but not among men. These demographic factors explain a sizable fraction of the gender gap in employment, but they explain no more than 6 percent of the gender wage gap. Differences in constraints, mainly in the form of the mean offered wages and rates of job arrival and destruction, explain most of the gender wage gap. Policy simulation results suggest that, relative to reducing the wage cost of part-time work, providing additional employment protection to part-time jobs is more effective in reducing the gender wage gap.
Keywords: 330